Attitudes of clinicians toward cardiac surgery and trisomy 18. Issue 3 (28th January 2019) - Kaulfus, Meagan E.; Gardiner, Helena; Hashmi, S. Shahrukh; Mendez‐Figueroa, Hector; Miller, Victoria J.; Stevens, Blair; Carter, Rebecca
Abstract: Trisomy 18 is an autosomal trisomy condition characterized by minor to major birth defects, severe disabilities, and high rates of pre‐ and postnatal mortality. Interventions for these infants have traditionally been withheld with focus instead on palliative support. The issues and attitudes surrounding corrective surgery of congenital heart defects, which is a birth defect that occurs in approximately 90% of infants with trisomy 18, is of our study's interest as recent literature has indicated that cardiac surgery is being performed and may lead to improved survival compared to palliative care. Thus, our study aimed to describe clinician attitudes toward cardiac surgery and trisomy 18. We surveyed 378 clinicians from multiple specialties, including genetic counselors, involved in the pre‐ and postnatal care of infants with trisomy 18. Descriptive statistics were performed to describe all clinicians' responses, and a secondary analysis with stratifications by clinician type was also performed. Forty‐eight percent ( n  = 378) of clinicians felt it was appropriate to discuss the option of cardiac surgery. Ethical concerns and insufficient outcome data were the most agreed upon reasons for not offering cardiac surgery. Trisomy 18 not being uniformly lethal and expressed parental wishes were the most agreed upon justifications for offering surgery. Clinicians felt the discussion of the option of cardiac surgery is appropriate, however are hesitant due to ethical concerns and insufficient outcome data. Results from this study aim to promote discussion and collaboration among clinicians to improve consistency in patient care.